The impact of the “mãe curitibana” program on the mother-To-child transmission of HIV In Curitiba be tween 2000 and 2009 - Burger, Marion; Pchebilski, Lourdes Terezinha; Sumikawa, Elaine S; Sakurada, Elina MY; Telles, Tatiane MBB; Parabocz, Michele; Cubas, Raquel F; Luhm, Karin Regina; Jimenez, Edvin Javier Boza (Brazilian Journal of Sexually Transmitted Diseases, 2011)
Introduction: the majority of diagnoses of HIV infection in women occur during pregnancy and the mother-to-child transmission is the main form of HIV infection in children. Therefore, prenatal care represents an excellent opportunity for prophylaxis, because without intervention measures during pregnancy, the rate of HIV transmission reaches 30%. Objective: this study describes the actions of the “Mãe Curitibana” Program in relation to HIV positive pregnant women and the mother-to-child HIV transmission. Methods: retrospective analysis of 2000 to 2009 assistance and reporting data of HIV positive pregnant women living in Curitiba. Results: it is estimated that among the 1,169 HIV positive pregnant women reported in this period could occur 350 vertical infections. In this context, a total of 44 infected infants in these 10 years show that interventions to prevent transmission contributed to avoid a total of 306 vertically HIV infected children in Curitiba. Measures such as decentralized HIV testing of pregnant women, parturient and partners, referrals to specialized treatment, so as antiretroviral medication during pregnancy, childbirth and the newborn, the inhibition of lactation and postpartum and childcare follow-up have been effective for this reducing transmission. With effort, the transmission rate in 1999 was at 5.1% and reduces to 2.5% in 2009. Conclusion: the early capture of pregnant womens, the organization of flowcharts, rapid intervention measures, treatment adherence, monitoring of children and women are actions of the “Mãe Curitibana” Program that has helped in reducing mother-to-child transmission of HIV.